(Tidak) Demokrasi ala Asia - Hiariej, Eric (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 1997)
The discussion about democracy generally comes to the perspective differences at the philoshopical level. Despite these differences, some political experts are quite optimistic on the future of democracy in many countries. This optimism lies on the fact that there has been a consensus to measure democracy at the practical level. Based on this background, Neher and Marlay use Procedural democratic criterias to hightight the mozaic of democracy in Asian countries. Both fall to the conclusion that Asian democracy posseses a unique characteristic, which is called